Directive Speech in TikTok Live Commerce Ahead of Eid al-Fitr: A Pragmatic Analysis of Promotional Language Strategies - Desi Novita Sari; Victor Piores (Universitas Negeri Semarang, 2026)
The live commerce phenomenon on the TikTok platform is experiencing rapid growth, especially ahead of Eid al-Fitr, a period marked by increased promotional activity and public consumption. This study aims to describe the form of directive speech and promotional language strategies used in TikTok live broadcasts. The research uses a pragmatic approach with a qualitative descriptive method. The research data consisted of 33 speeches obtained from five live commerce sessions on the TikTok @elzattahijab account. The account was chosen purposively because it actively uses live commerce features to promote Muslim fashion products and demonstrates intensive interaction between hosts and audiences ahead of Eid al-Fitr. Data is collected through record, listen, and record techniques, then analyzed based on the context of its use. The results of the study show that directive speech is the dominant form of speech used in live commerce activities. Speech is realized in the forms of the imperative, interrogative, and declarative, which convey the intention of directing the audience to certain actions. In addition, various promotional language strategies were found to accompany directive speech actions, including urgency, social closeness, seasonal (Eid al-Fitr), and profit-based strategies. These findings show that directive speech actions and promotional language strategies support each other in building persuasive communication during live broadcasts. Thus, the use of language in live commerce not only serves to convey product information, but also serves as a means to build audience engagement and direct their actions in the context of digital promotion.